Youth’ Co-Creation Behavior in Casual Dining Restaurants in Bandung City, Indonesia - Pri Hermawan; Utomo Sarjono Putro; Dini Turipanam Alamanda; Dewi Riani (Jurnal Manajemen Indonesia, 2022)
This study aims to identify the co-creation behavior especially students who have experiences of casual dining restaurants. This study also analyses the relationship between co-creation behavior, customer satisfaction, and customer loyalty. The research applied a quantitative method with survey design, and it was conducted for 6 months. It applied the purposive sampling method and the questionnaires were distributed to 1,970 respondents. The collected data were analysed using Structural Equation Modelling (SEM). The results indicate that two types of co-creation behavior of students who have experiences of casual dining restaurants in Bandung, namely customer participant behavior and customer citizenship behavior.Keywords: consumer behaviour; culinary; co-creation behaviour; satisfaction; loyalty